Eksistensi Perum Damri dalam Upaya Menjaga Stabilitas Ekonomi Nasional - Pahlevi, Farida Sekti (Institut Agama Islam Sunan Giri Ponorogo, 2022)
Perum DAMRI is expected to be able to provide public transportation services that comply with the principles of Traffic and Road Transportation in the Law of the Republic of Indonesia Number 14 of 1992 concerning LLAJ, namely safety, accuracy, regularity, comfort, speed, and satisfaction. The existence and service performance of Perum DAMRI has experienced various problems from the early years of its establishment to the present. Starting from the decrease in the number of passengers, business competition, to the decline in service quality. This study uses a qualitative descriptive method in discussing the extent of the existence of Perum DAMRI, the problems and innovations carried out as one of the BUMNs that play a role in national economic stability. The results of this study describe the safety, accuracy, regularity, convenience, speed, and satisfaction of Public Transportation Perum DAMRI City Bus Transportation Unit experiencing a decline condition. Its role is slowly starting to decline due to the emergence of various kinds of competitors, namely the private sector which continues to innovate. However, in such conditions PERUM DAMRI continues to innovate and set new strategies so that it can always carry out its vision, mission and functions in accordance with applicable regulations.